FeCl2-catalyzed rearrangement of aryl peroxyoxindole into 1,3-benzooxazin-4-One - Mohanta, Nirmala; Samal, PragnyaParamita; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Advanced Synthesis & Catalysis, 2023)
We report an FeCl2-catalyzed radical rearrangement of aryl peroxyoxindoles into 1,3-benzooxazin-2-ones to obtain a variety of aryl substituted 1,3-benzooxazin-4-ones in moderate to good yields. Mechanistically, this skeletal rearrangement of peroxyoxindoles proceeded via radical pathway and was well supported with a series of experimental findings and DFT studies.
Keywords: 1; 3-Benzooxazin-4-one; FeCl2; Peroxyoxindole; rearrangement; Ring expansion

Access to NHC-Boryl mono- and bis-selenide and utility as mild selenium transfer reagent including to the C-F bond - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (Chemistry- a european journal, 2024)
Reactions of 5-SIDipp & sdot; BH3 (5-SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene) (1) with diphenyldiselenide provide access to 5-SIDipp-boryl mono- (5-SIDipp & sdot; BH2SePh) (2) and bis-selenide (5-SIDipp & sdot; BH(SePh)2) (3). The facile cleavage of the B-Se bond makes 2 a neutral source of selenium nucleophiles in substitutions reactions with benzyl bromides, and provide access to the corresponding selenoethers. The direct transformations of one of the C(sp2)-F bonds of C5F5N and C6F5CF3 to C-Se bonds have also been achieved by the use of 2 without employing transition-metal catalysts. While it was previously established that C6F6 could undergo complete defluoroselenation under harsh conditions, we successfully achieved partial defluorination of C6F6 by employing 2 as a mild selenide transfer reagent. During the formation of C-Se bonds through the cleavage of C-F bonds, the potential by-product NHC & sdot; BH2F undergoes ring expansion of the NHC, leading to the formation of the six-membered diaazafluoroborinane (7). Access to NHC & sdot; boryl mono- and bis-selenides from NHC & sdot; BH3 has been achieved. The boryl mono selenide has been demonstrated to function as a selenium transfer reagent, enabling the synthesis of selenoethers from benzyl bromide. Additionally, it can also facilitate the conversion of the challenging aromatic C-F bond to a C-Se bond, resulting in concomitant ring expansion of NHC & sdot; haloborane.image
Keywords: boron; C-F Bond Activation; N-Heterocyclic carbene; Ring expansion; Selenium